A non-fullerene acceptor with a fully fused backbone for efficient polymer solar cells with a high open-circuit voltage. Issue 39 (23rd September 2016) - Li, Shuixing; Liu, Wenqing; Li, Chang-Zhi; Lau, Tsz-Ki; Lu, Xinhui; Shi, Minmin; Chen, Hongzheng
Abstract : A planar perylene diimide derivative with a high efficiency of 7.33% and high voltage of 0.99 V is presented. Abstract : Herein, we design and synthesize a perylene diimide derivative with a fully fused backbone, FITP, which possesses an elevated lowest unoccupied molecular orbital level and high electron mobility. Consequently, polymer solar cells with FITP as the acceptor can provide the best efficiency of 7.33% with a high voltage of 0.99 V.